A SUCCESSFUL REPOSITION OF VAGINAL PROLAPSE IN CORRELATION WITH BIOCHEMICAL PROFILE IN CATTLE. - RAMSINGH, L; KUMAR D, ASHOK; BABU B, RAJA (The Indian Journal of Animal Reproduction, 2021)
The vaginal and uterine prolapse are common obstetrical problems among pregnant cattle and buffaloes during the last quarter of gestation. In the present case, replacement of vaginal prolapse with Buhner’s sutures and biochemical profile during 8th month of gestation is discussed. After application of mimosa pudica on the protruded prolapsed mass prolapse was repositioned and applied bhuner sutures. The biochemical profiles revealed that the concentrations of total protein (5.8 g DL), calcium ( 8.2 mgDL) and phosphorus ( 3.8 mgDL) were lower than the referral values of the normal pregnant cows. Based on these values cows were treated with calcium, phosphorous and astymin intravenously for 5 days and the animal was recovered unevenly and also delivered a calf after full length of gestation.